Decision to delivery interval in emergency LSCS and its impact on fetal outcome - Nair, Vidhu V.; Nair, Sobha S.; Venugopalan, Prasanna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Emergency LSCS can be categorized based on RCOG guidelines into category I and II which indicates maternal or fetal compromise. Here an urgent delivery and the DDI (decision to delivery interval) within 30 and 45 minutes respectively is needed. Methods: This is a retrospective cross-sectional analysis conducted on a sample of 630 patients who underwent caesarean section over a year, from June 2016 to June 2017. The DDI were further classified into ≤30 and >30 minutes for category I, ≤45 and >45 minutes for category II LSCS. The primary objective is to determine whether DDI in Category I and II emergency LSCS has an impact on fetal outcome and secondary objective is to ensure that DDI is within the standard criterion as per RCOG protocol. Results: Out of 630 samples of caesareans, it was found that 173 falls in Category I and 189 falls in Category II. Out of 87 (50.29%) patients delivered within 30 minutes in Category I, 29 babies required NICU admission. DDI was more than 30 minutes in 86 (49.71%) cases in Category I out of which 38 babies got admitted in NICU with low APGAR scores. Out of 176 (93.12%) patients who delivered within 45 minutes in Category II, 56 babies required NICU admission. DDI was more than 45 minutes in 13 (6.88%) cases in Category II and all these babies got admitted in NICU. Conclusions: Decision -delivery interval has a significant impact on fetal outcome.